Wplyw efektywnosci instytucji w kontekscie gospodarki opartej na wiedzy na jakosc zycia w Unii Europejskiej. Badanie panelowe dla lat 2004-2010 - Adam P. Balcerzak; Michal Bernard Pietrzak (Institute of Economic Research (IER), 2015)
– The article concentrates on the problem of the efficiency of the institutional system of the European Union countries in relation to the potential of the knowledge-based economy (KBE) and its impact on quality of life. In order to define the efficiency of the institutional system, the authors refereed to the analytical structure of the new institutional economics, in particular, the transaction costs theory. On this basis, it is assumed that effective institutional factors are conducive to the reduction of transaction costs. To measure the effectiveness of the institutional system authors proposed a synthetic indicator, which has been constructed with application of the modified TOPSIS method. As diagnostic variables the authors adopted the variables on four aspects characterizing the efficiency of the institutional system in the context of the country's ability to exploit the potential of KBE. The aspects were related to regulations aimed at promoting entrepreneurship, the issue of law institutions conducive to maintaining low level of transaction costs and improving the efficiency of the market mechanism, the issue of economy competitiveness and efficiency of labor markets and the quality of financial market institutions. The data were obtained from the database of Fraser Institute that is created for the purpose of the annual Economic Freedom of the World report. For the measurement of quality of life the Human Development Index was used. The main aim of this article was an attempt to assess the relationship between the level of institutional effectiveness in the context of KBE and quality of life for residents of the European Union countries in 2004-2010. In the econometric analysis the dynamic panel model was used for the 24 countries of the European Union, which has led to the identification of the positive impact of the efficiency of the institutions on the quality of life.
Keywords: 330; effectiveness of the institutional system; quality of institutions; theory of transaction costs; quality of life; Human Development Index; knowledge-based economy; TOPSIS; dynamic panel model